2006
DOI: 10.2147/ciia.2006.1.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline (Cognizin) in the treatment of cognitive impairment

Abstract: Pharmacological treatment of cerebrovascular disorders was introduced at the beginning of the 20th Century. Since then, a multitude of studies have focused on the development of a consensus for a well defined taxonomy of these disorders and on the identification of specific patterns of cognitive deficits associated with them, but with no clear consensus. Nevertheless, citicoline has proved to be a valid treatment in patients with a cerebrovascular pathogenesis for memory disorders. A metanalysis performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
0
50
0
1
Order By: Relevance
“…In studies with CDP-choline administered up to 12 months, it showed excellent tolerability and safety, with a few transient (never severe) adverse effects (e.g. stomach pain, diarrhea) (Conant et al 2004;Fioravanti et al 2006;Saver 2008). A "double dummy" procedure was used with participants being administered 4 capsules in each session so that the dose remained blind (e.g.…”
Section: Cdp-cholinementioning
confidence: 99%
See 1 more Smart Citation
“…In studies with CDP-choline administered up to 12 months, it showed excellent tolerability and safety, with a few transient (never severe) adverse effects (e.g. stomach pain, diarrhea) (Conant et al 2004;Fioravanti et al 2006;Saver 2008). A "double dummy" procedure was used with participants being administered 4 capsules in each session so that the dose remained blind (e.g.…”
Section: Cdp-cholinementioning
confidence: 99%
“…5'-citidine diphosphocholine or CDP-choline (citicoline) is a dietary supplement which acts as a key intermediate in the biosynthesis of phosphatidylcholine from choline (Secades et al 1995). CDP-choline has been shown to improve impaired cognition associated with chronic ischaemia, head trauma, dementia and normal aging (Alvarez-Sabin and Roman 2011; Conant and Schauss 2004;Davalos et al 2012;Fioravanti and Buckley 2006;Garcia-Cobos et al 2010;Secades 2012). In a 16-week trial combining CDP-choline with the positive allosteric modulator (PAM) of the α7 and α4/β2 nAChRs, galantamine, clinical symptoms of SZ patients were unaffected but overall functional level of patients was increased, as was performance on a test of free verbal recall (Deutsch et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effect size was large (OR, 8.89; 95% CI, 5.19 -15.22; PϽ0.001), indicating a strong drug effect for improvement with active treatment. 35,36 These authors concluded that the cognitive effects of citicoline are clearly evident at the behavioral level and can be easily appreciated with a clinical observation of patients irrespective of the functional paradigm used to measure them. Citicoline is remarkably welltolerated and more side effects were seen with the placebo than with the active treatment groups.…”
Section: Citicoline In Stroke and Cognitive Declinementioning
confidence: 99%
“…Citicoline is remarkably welltolerated and more side effects were seen with the placebo than with the active treatment groups. 35,36 Experimental and clinical studies have shown that citicoline effects may result from its contribution to several mechanisms of neuroplasticity and neurorepair. Regarding plasticity, Hurtado et al 28 showed that chronic treatment with citicoline improved functional recovery after experimental stroke and, more importantly, demonstrated that a potential neuronal substrate for the improvement of function could be the enhancement of dendritic complexity and spine density compared with the saline control group.…”
Section: Citicoline In Stroke and Cognitive Declinementioning
confidence: 99%
“…4,5) CDP-choline is a raw material for the synthesis of phospholipids, which are cell-membrane components required to maintain the structure of nerve cells. 6) However, the memory enhancing effect of CDP-choline may be due to increasing the supply of acetylcholine, because CDP-choline increases extracellular acetylcholine in the dorsal hippocampus and neocortex in normal rats.…”
Section: Introductionmentioning
confidence: 99%